Socio-economic Factors Responsible for Delayed Presentation of ROP in a Tertiary Neonatal Care Unit in Bangladesh (Journal of National Institute of Ophthalmology, 2023)
Purpose: To evaluate the socio-economic factors responsible for delayed presentation of ROP in a tertiary neonatal care unit in Bangladesh.Methods: This observational study was conducted on fifty babies, who were presented delay at screening were purposively selected for the study at Dhaka Shishu Hospital, National Institute of Ophthalmology & Hospital. Study period was 12 months and data collection was done by face to face interview from legal guardians with pre designed questionnaire. Information regarding gestational age, birth weight, condition of health at birth,parents education level and economic condition were obtained by face to face interview from parents. They were also asked whether the baby was advised for screening or not. Screening was done by indirect ophthalmoscopy by using 20D condensing lens.Results: Among the 50 babies, prevalence of ROP was 66.0% (95% CI: 52.87-79.13). Mean gestational age was 29.10(±1.5) weeks and mean birth weight was 1250(±0.24) gm. After taking account of all possible confounders, we found that place of residence of the parents is associated (p=0.011) as well as adviced for screening is marginaly assocated (p= 0.05) with delayed presentation of ROP for screening.Conclusion: There are many risk factors for delayed presentation of ROP at screening. Among the factors palce of residence (rural) and advice for screening are found to be significant. Further study regarding this issue is necessary to explore all other factors and formulate plans to overcome them.J.Natl.Inst.Ophthalmol.2023;6(1): 9-15